PERAN ORANG TUA DAN POLA ASUH TERHADAP KESADARAN LITERASI MEMBACA PADA SISWA KELAS III SD NEGERI 1 WATUBELAH - Shifa Istianah Azzahra; Asih Wahyuningsih; Prabawati Nurhabibah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is an important means to develop students' potential, one of which is through reading literacy. However, students' reading interest in Indonesia is still relatively low, as shown by the PISA survey results, which show that Indonesian students' reading ability is below the average for OECD countries. At SD Negeri 1 Watubelah, a literacy program has been implemented, but the reading interest of grade IIIA students is still low. The contributing factors include lack of motivation, the influence of technology, and minimal reading support in the family environment. This study aims to describe the role of parents and their parenting styles on the reading literacy awareness of grade III students at SD Negeri 1 Watubelah. The method used is descriptive qualitative with data collection techniques such as observation, interviews, and documentation. The research subjects included grade IIIA students and parents. The results show that the active role of parents in accompanying, providing motivation, and providing reading facilities at home can increase children's interest and awareness in reading. Democratic parenting styles have been proven to be more effective in forming reading habits in children compared to authoritarian and permissive parenting styles. These findings emphasize the importance of collaboration between parents and schools in building a culture of literacy from an early age.